Pemikiran Mahmud Muhammad Thaha tentang Syariat yang Humanis - Azwarfajri Azwarfajri (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2013)
Mahmud Muhammad Thaha, a Sudanist Islamic thinker, tries to issue a  new Islamic perspective on Islamic law. According to him, Islam has two main  periods; Mecca period (610-622M.) and Medina period (623-632M). The former,  called al-risalah al-ula and the latter, called al-risalah al-thaniyah. The nuances  of al-risalah al-ula it is universal, substantive, protective the all mankind, equal  and democratic. Whereas al-risalah al-thaniyah it becomes “established Islam”  and protected the internal ummah with locally and temporarily additional rules.  Some additional rules are not derived from the original sources of Islam, the  Qur’an and hadith. Therefore, according to Thaha, Islamic law needs to be  reformed in order to adjust it to the demands of modern time so that Islamic law  play sicnificant role in the formation of humanist and democratic world.